IMPLEMENTASI PROGRAM MAKAN SIANG BERSAMA UNTUK STIMULASI KEMANDIRIAN MAKAN SENDIRI ANAK USIA 4-5 (STUDI KUALITATIF DESKRIPTIF DI BUNAYYA ISLAMIC PRE SCHOOL) - Shakilla Salafia Kayla; Isti Rusdiyani; Dian Surya Aprilyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Independence is a crucial aspect of development that requires stimulation from an early age through meaningful learning experiences. One activity with the potential to foster children's independence is the communal lunch program regularly implemented in early childhood education institutions. This study aims to describe the implementation of the communal lunch program in stimulating the independence of children aged 4–5 years at Bunayya Islamic School Jakarta, identify the forms of independence that develop, and analyze the factors supporting and hindering its implementation. The study employs a qualitative approach with a case study design. The research subjects consisted of the school principal, teachers of the 4–5 age group, and children aged 4–5 participating in the lunch program. Data collection was conducted through observation, semi-structured interviews, documentation, and field notes. Data analysis utilized the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The results indicate that the communal lunch program is implemented in a structured manner, involving activities such as handwashing, praying, serving food according to needs, eating together, and tidying up eating utensils afterward. The program effectively stimulates the development of self-help skills, simple decision-making abilities, self-regulation, responsibility, and social interaction among the children. Program success is supported by consistent habituation, teachers acting as role models, and adequate facilities and infrastructure; conversely, hindering factors include varying levels of independence among the children and a lack of consistent habituation within the family environment. Thus, the communal lunch program serves as an effective habituation-based learning strategy for stimulating independence in early childhood. Keywords: lunch program implementation, child independence, habit formation, early childhood education.